Quinine induces reversible high-tone hearing loss. - Roche, R; Silamut, K; Pukrittayakamee, S; Looareesuwan, S; Molunto, P; Boonamrung, S; White, N (1990)
Serial audiometry was performed in ten patients receiving quinine treatment for acute falciparum malaria. Quinine reduced high tone auditory acuity in all patients, resulting in flattening of the audiograms. The effect was rapid in onset, usually unnoticed (although tinnitus was reported in seven patients), and resolved completely after treatment was completed.